ANALYSIS OF 6C SKILLS (CRITICAL THINKING, CREATIVITY, COLLABORATION, COMMUNICATION, COMPUTATIONAL THINKING, COMPASSION) IN THE IMPLEMENTATION OF 21ST CENTURY LEARNING IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT SMK UNGGUL NEGERI 2 BANYUASIN III - Nurjana, Nurjana; Ismail, Fajri; Fitrianti, Yuli (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to analyze the implementation of 6C skills Critical Thinking, Creativity, Collaboration, Communication, Computational Thinking, and Compassion in Islamic Religious Education (PAI) as part of 21st-century learning at SMK Unggul Negeri 2 Banyuasin III. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and document analysis involving PAI teachers, the principal, and students. The findings reveal that the integration of 6C skills is evident, particularly in aspects of collaboration and communication through group discussions and student presentations. However, the application of computational thinking and creativity remains limited due to challenges such as uneven technology integration and reliance on conventional teaching methods. Supporting factors include adequate technological infrastructure and a school culture that upholds religious values, while major obstacles involve the lack of teacher training in innovative learning strategies. The study concludes that optimizing 6C competencies in PAI instruction requires enhancing teachers’ pedagogical skills, ensuring equitable access to digital tools, and strengthening school-industry partnerships to prepare students who are adaptive, ethical, and globally competitive.